Actividades lúdicas para el mejoramiento de la lectura comprensiva de los estudiantes de quinto año de Educación Básica de la escuela " Numa Pompillo Llona". - Tello Cóndor, Gina de las Mercedes (2021)
This project is part of the problem of the deficient level of comprehensive reading that students of the Fifth Year of Basic Education have at the Numa Pompilio Llona School. The objective under which the project was developed was to develop a program of recreational activities for the improvement of comprehensive reading in students, taking into consideration that recreational activities represent a pedagogical tool that contributes to enhancing the acquisition of knowledge and the development of skills in the learner, improving aspects such as motivation, predisposition, participation, active and also allows to relate the contents approached with positive emotional charges. The methodology used in the development of the research is framed in the qualitative-quantitative approach, through the application of the survey technique directed to teachers and students, complemented with the applied modality since a proposal adjusted to the dimensions and characteristics of the problem within the Numa Pompilio Llona Basic Education School. The main results show that using playful strategies significantly amplifies the improvement of comprehensive reading in students, contributing to learning and academic performance